2013
DOI: 10.3727/096368913x672127
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term outcome of Olfactory Ensheathing Cell Transplantation in Six Patients with Chronic Complete Spinal Cord Injury

Abstract: The aim of the study was to analyze the clinical efficacy and safety of olfactory ensheathing cell (OEC) transplantation for treating patients with chronic, complete spinal cord injury (SCI). Six patients with six chronic complete spinal cord injuries were recruited and treated with autologous OEC transplantation and followed for 24 months. The scores from before and after transplantation were analyzed. This was a self-control experiment. There was significant amelioration in the scores of the standard neurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…It has also reported that OECs improve local microcirculation of the damaged spinal cord and promote angiogenesis, thus enhancing remyelination of demyelinated neuronal axons [ 30 , 31 ]. According to previous work, OECs transplantation is clinically safe [ 32 , 33 ] and offers promising therapeutic outcomes for patients [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also reported that OECs improve local microcirculation of the damaged spinal cord and promote angiogenesis, thus enhancing remyelination of demyelinated neuronal axons [ 30 , 31 ]. According to previous work, OECs transplantation is clinically safe [ 32 , 33 ] and offers promising therapeutic outcomes for patients [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell therapies are only used experimentally [10]. Various cell therapies, such as the use of OSCs, have been tested in the last decade [19,[42][43][44][45][46]. Transplanted olfactory cells promoted tissue nerve regeneration by paracrine signaling and by creating a conductive environment [47].…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, the clinical application of olfactory ensheathing glia (OEG) for the treatment of SCI was evaluated in 8 participants. 92 Interestingly, a return of substantial sensation and motor activity in specific muscles below the injury site was observed in a few participants as well as improved bladder function. Importantly, no serious complications of the cell therapy were observed.…”
Section: Reparative Strategiesmentioning
confidence: 93%